An alternative plant-based fermented milk with kefir culture using apricot (Prunus armeniaca L.) seed extract: Changes in texture, volatiles and bioactivity during storage - Uruc, K.; Tekin, A.; Sahingil, D.; Hayaloglu, A. A. (Elsevier Sci Ltd, 2022)
The aim of the study was to produce kefir from apricot seed extract (ASE) as an alternative functional dairy food for vegans and lactose-intolerant people, the elderly, people with cardiovascular disease and diabetes. Kefir was produced by using cow's milk (100%, as control) and 100% ASE, and cow's milk was mixed with 25%, 50% and 75% (v/v) with ASE for kefir production and the resultant kefir samples were stored at 4 degrees C for 21 days. In proportion to the level of ASE, more yellowish color, lower viscosity, firmness, consistency and TPA values were developed. Additionally, a higher syneresis was observed in kefir samples with increasing levels of ASE. Angiotensin-converting enzyme-inhibitory (ACE-i) and antioxidant activities increased with the increasing levels of ASE used in the kefir production. The levels of individual free amino acids significantly changed by use of ASE and some amino acids including Gln, Gly and Arg dramatically increased, while others decreased by increasing levels of the ASE. Relatively lower levels of gamma-amino butyric acid (GABA) were observed in the samples when compared to the free amino acids, and its concentration decreased by increasing levels of the ASE. The counts for yeasts, lactobacilli and lactococci increased with addition of ASE. Qualitative and quantitative differences were seen in volatile composition of kefir with the addition of ASE and acceptable sensory scores were obtained for all samples during storage. Concentrations of carboxylic acids decreased with increasing levels of ASE in kefir formula; however, the levels of alcohols and aldehydes increased. In conclusion, ASE can be considered in the formulation of fermented milk products or used purely in the production of plant-based fermented non-dairy beverages.
Keywords: Plant-based milk; Gamma-amino butyric acid; Free amino acid; Apricot seed extract; Kefir; Vegan nutrition; Bioactivity